2010
DOI: 10.1158/0008-5472.can-09-2951
|View full text |Cite
|
Sign up to set email alerts
|

The Somatostatin Analogue Octreotide Confers Sensitivity to Rapamycin Treatment on Pituitary Tumor Cells

Abstract: Rapamycin and its analogues have significant antiproliferative action against a variety of tumors. However, sensitivity to rapamycin is reduced by Akt activation that results from the ablative effects of rapamycin on a p70 S6K-induced negative feedback loop that blunts phosphoinositide 3-kinase (PI3K)-mediated support for Akt activity. Thus, sensitivity to rapamycin might be increased by imposing an upstream blockade to the PI3K/Akt pathway. Here, we investigated this model using the somatostatin analogue octr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 55 publications
7
79
0
3
Order By: Relevance
“…Administration of RAD001 to MENX PA cells in primary culture also resulted in a dose-dependent reduction in cellular viability that reached significance at a dose of 100 nM in 45% of their sample (five out of 11 cultures; Lee et al 2011). Finally, Cerovac et al (2010) exposed 28 human NFPAs in primary culture to rapamycin and reported a small (!20%) reduction in cellular proliferation in 29% (eight of 28 tumors) of their samples.…”
Section: Current Mtor Inhibitorsmentioning
confidence: 96%
See 3 more Smart Citations
“…Administration of RAD001 to MENX PA cells in primary culture also resulted in a dose-dependent reduction in cellular viability that reached significance at a dose of 100 nM in 45% of their sample (five out of 11 cultures; Lee et al 2011). Finally, Cerovac et al (2010) exposed 28 human NFPAs in primary culture to rapamycin and reported a small (!20%) reduction in cellular proliferation in 29% (eight of 28 tumors) of their samples.…”
Section: Current Mtor Inhibitorsmentioning
confidence: 96%
“…These findings were attributed to decreased levels of mTOR phosphorylation at the serine-2448 residue, which is a key determinant of mTOR activity. A third study noted a small Greater antiproliferative effect than RAD001; triggers apoptosis Lee et al (2011) but statistically significant antiproliferative effect of 1 nM rapamycin on mouse AtT20 cells and no effect at lower doses (Cerovac et al 2010). Musat et al (2005) have reported that NFPAs have the highest levels of AKT mRNA expression of all PA subtypes.…”
Section: Current Mtor Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The anti-proliferative effect of an mTOR inhibitor on different pituitary cell lines or primary cultures has been demonstrated in vitro (Cerovac et al 2010). In vitro data have also shown an effect of everolimus on cell viability in cell cultures from non-functioning pituitary adenomas (Zatelli et al 2010).…”
Section: Molecular Targeted Treatmentmentioning
confidence: 97%